2017
DOI: 10.1123/jsep.2017-0112
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions, Trait Self-Control, and the Intention–Behavior Gap in Physical Activity Behavior

Abstract: Many people fail to translate their physical activity intentions into behavior. This intention-behavior gap can be explained by (a) explicit trait self-control, (b) implicit executive functions, and (c) their interactions. In 118 participants, the intention-behavior gap was measured in a prospective design. Trait self-control was assessed via self-report questionnaires, whereas executive functioning was measured with test performance in inhibition, updating, and shifting at baseline. Regression analysis showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 54 publications
3
53
1
Order By: Relevance
“…Although several psychological theoretical models (e.g., Theory of Planned Behavior; Ajzen, 1991 ) have been used to guide research, a common finding is that despite individuals’ good intentions to be physically active they often do not translate these intentions into behavior, referred to as the “intention-behavior” gap ( Rhodes and Bruijn, 2013 ; also see Sheeran and Webb, 2016 ). Research based on the Strength Model has proposed, and provided initial evidence, that one of the reasons people fail to translate their intentions into behavior is a result of prior exertions of HCC ( Martin Ginis and Bray, 2010 ; Englert and Rummel, 2016 ; Pfeffer and Strobach, 2017 ; Schöndube et al, 2017 ). Thus, given the global physical inactivity epidemic, alongside self-efficacy’s role in predicting physical activity behavior ( McAuley and Mihalko, 1998 ; Sallis et al, 2016 ), findings from the present study provide a new avenue of research for understanding inactivity patterns that may also be attributed to reductions in self-efficacy that occur following the exertion of cognitive control on previous, unrelated, tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several psychological theoretical models (e.g., Theory of Planned Behavior; Ajzen, 1991 ) have been used to guide research, a common finding is that despite individuals’ good intentions to be physically active they often do not translate these intentions into behavior, referred to as the “intention-behavior” gap ( Rhodes and Bruijn, 2013 ; also see Sheeran and Webb, 2016 ). Research based on the Strength Model has proposed, and provided initial evidence, that one of the reasons people fail to translate their intentions into behavior is a result of prior exertions of HCC ( Martin Ginis and Bray, 2010 ; Englert and Rummel, 2016 ; Pfeffer and Strobach, 2017 ; Schöndube et al, 2017 ). Thus, given the global physical inactivity epidemic, alongside self-efficacy’s role in predicting physical activity behavior ( McAuley and Mihalko, 1998 ; Sallis et al, 2016 ), findings from the present study provide a new avenue of research for understanding inactivity patterns that may also be attributed to reductions in self-efficacy that occur following the exertion of cognitive control on previous, unrelated, tasks.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a global physical inactivity epidemic occurring among children ( Tremblay et al, 2014 ; Sallis et al, 2016 ) making them susceptible to various negative health outcomes as they age. Thus, research investigating the effects of cognitive control exertion on physical activity behavior among children serves as a potential new avenue for understanding inactivity patterns recently observed among young adults ( Pfeffer and Strobach, 2017 ; Rebar et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Results from studies using a neutral go/no-go task to explain physical activity are inconclusive. One study observed that better performance (i.e., faster reaction times in go trials) on a go/no-go task was associated with higher self-reported physical activity behaviors (Hall, Fong, Epp, & Elias, 2008), whereas a more recent work did not observe such associations (Pfeffer & Strobach, 2017). However, these studies investigated general inhibitory functions rather than inhibitory functions specifically associated with physical activity behaviors.…”
Section: Introductionmentioning
confidence: 98%
“…SR capacity has been conceptualized as including three component processes: executive functioning skills; emotion regulation strategies; and ability to delay gratification in service of achieving future goals [3,4]. Low SR capacity has been shown to interfere with individuals' engagement in a variety of health maintenance behaviors including engaging in regular physical activity [5], consuming a healthy diet [6][7][8], and adhering to medical treatment regimens [9][10][11].…”
Section: Introductionmentioning
confidence: 99%